The use of MALDI-TOF ICMS as an alternative tool for Trichophyton rubrum identification and typing - Pereira, Leonel João Pais (2014)
In this study, the potential of matrix-assisted laser desorption/ionization time-of-flight intact cell mass spectrometry (MALDI-TOF ICMS) was investigated for the identification of clinical isolates. The isolates were analyzed at the species and strain level,